LEGAL PROTECTION OF LAND RIGHTS HOLDERS AGAINST LAND OWNERSHIP DISPUTES - Lestari Siang, Indrawati; Hutomo, Putra; Rattanapun, Supot (Penerbit Lafadz Jaya, 2025)
This research aims to analyse the legal protection for land rights holders in Indonesia in the face of ownership disputes. Through a normative juridical approach, this research examines the regulation and implementation of legal protection, particularly in terms of land registration and proof of ownership. The findings show that legal protection has not been optimal due to limitations in the implementation of regulations, unclear administrative procedures, and low effectiveness of dispute resolution mechanisms. Reforms in the land registration system and the strengthening of related institutions are expected to improve legal certainty for land rights holders. This research contributes to the development of agrarian law with a focus on the protection of land ownership rights to ensure justice and legal certainty.